Nilai-Nilai Anti Korupsi dalam Pemikiran KH. Sahal Mahfudh dan Diseminasinya pada Perguruan Tinggi Pesantren - Nuraini, Latifah; Af'idah, Irma Nur; Afrida, Fira Nadliratul; Nasa'i, Maulana Irfan (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
The thoughts of KH. MA. Sahal Mahfudh in his fiqh sosial reflects anti-corruption values that are relevant to the main function of humans as Khalifatullah. This function implies two main tasks, namely Ibadatullah and Imaratul Ardh. This research aims to explore anti-corruption values in Kiai Sahal's thinking and its dissemination at the Mathali'ul Falah Pati Islamic Boarding School. The research method uses a qualitative approach with data collection through documentation, interviews, and observation. Interpretative analysis was used to explain Kiai Sahal's thoughts on anti-corruption values. The results showed that the thoughts of KH. MA. Sahal Mahfudh's contain anti-corruption values. Values such as ikhtiar, tawakal, honesty, transparency, amar ma'ruf nahi munkar, character, and integrity become the foundation in preventing corruption. At Institut Pesantren Mathali'ul Falah, these values are disseminated through anti-corruption policies and integrated in Shalih Akram's Basic Values (NDSA), such as al-Amanah, i'itimad ala nafsi, al kifah mudawamah, tawasuth, zuhud, istiqomah, and al-barakah. The academic community is expected to have an anti-corruption character that is reflected in the curriculum and courses of Pancasila Education and Anti-Corruption, Shalih Akram’s Basic Values (NDSA), and Social Jurisprudence.